(untitled) (Revista Electrónica REDINE, 2018)
The aim of the research article is to reconstruct the cultural and intercultural process based on the presence of the Canary Islands in Latin America and the Lara State, as this entity is a representation of the Canarian immigration issue from 1961 to 1981. In view of this, the resulting methodology is taken of the historical science and the foundations of the French School of Annales, through the use of primary and secondary sources to apply the historical method, which starts from defining the area under study, the time scale, the construction of a source bank for contextualize the historical reality and understand the social and institutional structures during the process of cultural syncretism generated through the Canarian reception, insertion and adaptation. It concludes the participation and effectiveness in the Canarian insertion in the Venezuelan society, resulting in a sustainable human, economic and cultural development within the Larense region, where it enhances the agricultural, irrigation and horticultural culture, and human, social values, religious, sporting, economic, productive and cultural.